THE MEANING OF BIOETHICS IN THE SITUATION OF MODERN ANTHROPOLOGICAL CRISIS - Makhmudova Aziza Nugmanovna (Journal of new century innovations, 2024)
Annotation: in today's article, Anthropology is a branch of biology that is very close to social sciences. Despite the fact that thoughts about anthropology appeared several thousand years ago, it began to take shape as a science only in the second half of the 19th century. An important field of anthropology - the department that studies the physiological, biochemical and genetic factors that affect the structure and development of the human organism - "Human biology" is explained.